Accounting Treatment of Digital Gold Transactions at BSI Mobile Sharia Perspective - Iin Istiyah (Indonesian Economic Review, 2026)
The digital transformation of Islamic banking has accelerated the development of mobile-based investment products, including digital gold services offered through BSI Mobile. Although gold trading has been normatively regulated under DSN-MUI Fatwa No. 77/2010, empirical studies examining the integration of sharia contracts and accounting treatment within real-time digital systems remain limited. This study aims to analyze the implementation mechanism of E-MAS transactions and evaluate their accounting treatment from the perspective of Islamic accounting standards. Using a qualitative case-study approach through observation, semi-structured interviews, and documentation analysis, the findings reveal that E-MAS transactions are conducted through electronic sale contracts applying constructive possession (qabd hukmi), supported by wadiah and ijarah contracts for custody and service components. Customers’ gold balances are classified as liabilities, while bank income is derived from service fees (ujrah). Although the practice generally aligns with PSAK 101, PSAK 102, and DSN-MUI Fatwa No. 77/2010, the application of existing standards remains interpretative due to the absence of specific accounting guidelines for digital gold products. This study conceptualizes digital gold transactions as a hybrid Sharia structure and highlights the need for adaptive Islamic accounting standards in the era of financial digitalization.